Glycated Hemoglobin as a Marker for Predicting Outcomes of Patients With Stroke (Ischemic and Hemorrhagic): A Systematic Review and Meta-Analysis - Bao, Yaya; Gu, Dadong (Frontiers in Neurology, 2021)
Background: Glycated hemoglobin (HbA1c) has emerged as a useful biochemical marker reflecting the average glycemic control over the last 3 months and the values are not affected by short term transient changes in blood glucose levels. However, its prognostic value in the acute neurological conditions such as stroke is still not well established. The present meta-analysis was conducted to assess the relationship of HbA1c with outcomes such as mortality, early neurological complications and functional dependence in stroke patients. Methods: A systematic search was conducted for the PubMed, Scopus and Google scholar databases. Studies, either retrospective or prospective in design, that examined the relationship between HbA1c with outcomes of interest and presented the strength of association in the form of adjusted odds ratio/hazard ratios were included in the review. Statistical analysis was done using STATA version 13.0. Results: A total of 22 studies (15 studies on acute ischemic stroke and 7 studies on hemorrhagic stroke) were included in the meta-analysis. For patients with acute ischemic stroke, each unit increase in HbA1c was found to be associated with an increased risk of mortality within one year, increased risk of poor functional outcome at 3 monthsand an increased risk of symptomatic intracranial hemorrhage (sICH) within 24 hours of admission. In those with HbA1c≥6.5%, there was an increased risk of mortality within one year of admission, increased risk of poor functional outcomes at 3 months and 12 months as well as an increased risk of symptomatic intracranial haemorrhage (sICH) within 24 hours of admission. In patients with hemorrhagic stroke, each unit increase in HbA1c was found to be associated with increased risk of poor functional outcome within the first three months from the time of admission for stroke. In those with HbA1c≥6.5%, there was an increased risk of poor functional outcome at 12 months. Conclusions: The findings indicate that glycated hemoglobin (HbA1c) could serve as a useful marker to predict the outcomes in patients with stroke and aid in implementation of adequate preventive management strategies at the earliest.